2009
DOI: 10.1007/s10681-009-9924-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat

Abstract: The 1BL.1RS wheat-rye translocation from Petkus rye has contributed substantially to the world wheat production. However, following the breakdown of disease resistance genes in 1RS, its importance for wheat improvement decreased. We have developed a new 1BL.1RS line, R14, by means of crossing rye inbred line L155, selected from Petkus rye to several wheat cultivars. One new gene each, for stripe rust and powdery mildew resistance, located on 1RS of the line R14, are tentatively named YrCn17 and PmCn17. YrCn17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 20 publications
1
85
0
3
Order By: Relevance
“…Several novel 1RS translocation lines or cultivars have been developed to maintain the yield traits and other excellent agronomic traits carried by the 1RS translocations, i.e., GRS1201 (Porter et al, 1994), 48112 and 89121 (Ji et al, 2008), R14 (Ren et al, 2009), and Mv9 kr1 (Molnár-Láng et al, 2010). These new translocation lines have recovered the resistance to diseases, but they have also expanded and enriched the available genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel 1RS translocation lines or cultivars have been developed to maintain the yield traits and other excellent agronomic traits carried by the 1RS translocations, i.e., GRS1201 (Porter et al, 1994), 48112 and 89121 (Ji et al, 2008), R14 (Ren et al, 2009), and Mv9 kr1 (Molnár-Láng et al, 2010). These new translocation lines have recovered the resistance to diseases, but they have also expanded and enriched the available genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…The 1BL.1RS translocation of CN10 and CN11 was inherited from the Russian wheat cultivar Aurora, which contains the gene Yr9 (Ren et al, 2009). …”
Section: Plant Materialsmentioning
confidence: 99%
“…Unfortunately, the frequency of 1BL.1RS translocation in recently released wheat cultivars has declined (Ren et al, 2009). The key to the problem lies in a narrow genetic base contributed by the 1RS arm from cv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1BL/1RS translocation lines, CN12 and CN17 studied in this research had been demonstrated to carry many valuable agronomic traits such as functional stay-green after anthesis and high disease resistance (Tang et al 2009;Ren et al 2009Ren et al , 2011. These translocations had been previously characterized using various cellular and molecular analyses (Luo et al 2006(Luo et al , 2013Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 96%